2021
DOI: 10.1007/s10896-021-00266-5
|View full text |Cite
|
Sign up to set email alerts
|

Saving Lives: Working across Agencies and Individuals to Reduce Intimate Homicide among those at Greatest Risk

Abstract: This special issue of the Journal of Family Violence offers insights on intimate homicide prevention from leading researchers and practitioners. The insights offered are timely, given the pervasiveness of domestic violence (DV), including some data since the emergence of COVID-19 noting an increase in DV-related  cases with severe  injury and police calls. Contributors in this special issue argue for interagency advocacy, protection orders, and firearm removal, along with reimagining dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…One of the most pertinent recommendations for decreasing IFs involves firearms. Bonomi et al, 2021 , suggested firearm removal from those legally restricted from accessing weapons and getting jurisdictions to create formalized protocols to ensure firearm relinquishment. In addition, Bonomi and colleagues ( 2021 ) call attention to applying an intersectional framework to how fatality review teams [FRT] are arranged and conducted.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the most pertinent recommendations for decreasing IFs involves firearms. Bonomi et al, 2021 , suggested firearm removal from those legally restricted from accessing weapons and getting jurisdictions to create formalized protocols to ensure firearm relinquishment. In addition, Bonomi and colleagues ( 2021 ) call attention to applying an intersectional framework to how fatality review teams [FRT] are arranged and conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Bonomi et al, 2021 , suggested firearm removal from those legally restricted from accessing weapons and getting jurisdictions to create formalized protocols to ensure firearm relinquishment. In addition, Bonomi and colleagues ( 2021 ) call attention to applying an intersectional framework to how fatality review teams [FRT] are arranged and conducted. According to the National Domestic Violence Fatality Review Initiative (2020), fatality reviews involve a deliberate process of examining domestic violence-related deaths to prevent future deaths.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although firearm fatality risk is six times higher for men, women are overrepresented among intimate partner homicides, with more than half resulting from firearms. [32][33][34] Finally, US cities are disproportionately affected by firearm homicide, whereas rural settings are disproportionately affected by firearm suicides. [35][36][37] Researchers have identified that although multiple firearm violence risk factors exist across all ecological levels, disparities are largely associated with underlying structural factors at the community and/or societal level.…”
Section: Disparitiesmentioning
confidence: 99%